Assessment of air pollutants removal by green infrastructure and urban and peri-urban forests management for a greening plan in the Municipality of Ferrara (Po river plain, Italy). (February 2022) - Muresan, Alexandra Nicoleta; Sebastiani, Alessandro; Gaglio, Mattias; Fano, Elisa Anna; Manes, Fausto
Highlights: Urban and peri-urban forests enhance the provision of regulating Ecosystem Services. PM10 and O3 removal by urban green areas was modeled in the Municipality of Ferrara. UGI annually remove 19.8Mg PM10 and 8.6 Mg O3, corresponding to € 2.12 million and € 147*10 3 . Reforesting current UGI would increase removal values by 49% for PM10 and 18% for O3 . Abstract: Air pollution is a serious concern for human health and is even more worrying in areas that are known to be "pollution hotspots", such as the Po Plain in northern Italy. The Urban Green Infrastructure (UGI), which includes urban and peri-urban forests, enhances human health and wellbeing delivering a wide range of ecosystem services, including air quality improvement. In this research, we analyzed, in biophysical and monetary terms, the role of the UGI in removing PM10 and O3 from the atmosphere in the Municipality of Ferrara using established removal models. We used a multiscale approach that includes geospatial data, field sampling and laboratory analysis. Then, using a local green areas database, we located public areas that could potentially undergo forestation actions without requiring any land conversion and evaluated the benefit in terms of ESs provision that these actions may exert. We found that, in 2019, the UGI in the Municipality of Ferrara removed about 19.8 Mg of PM10 and 8.6 Mg of O3, for a monetary benefit of € 2.12 million € and 147*10 3 respectively. We then identified about 121 ha within the urban core of the Municipality that could potentially be forested. Such an action would increase the PM10 and O3 removal by about 49% and 18%, respectively. Our findings comply with the EU Biodiversity strategy for 2030, which calls for the development of an ambitious greening plan for cities with more than 20, 000 inhabitants.